2011
DOI: 10.1016/j.jweia.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an upstream building on the wind-induced mean suction on the flat roof of a low-rise building

Abstract: The effect of an upstream building on the suction forces on the flat roof of a low-rise building placed in the wake of the former is analyzed. The analysis has been performed by wind tunnel testing of a flat roof, low-rise building model equipped with pressure taps on the roof and different block-type buildings (only configurations where the upstream building is as high or higher than the downstream one are considered in this paper). The influence of the distance between both buildings on the wind loads on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The electronic pressure-scanning module converts them to high-level electronic signals. This system is a globally proven equipment for wind tunnel experiments in the construction, civil, and aerospace fields [22][23][24][25]. This electronic pressure-scanning module can accurately measure unsteady pressure signals within a small margin of error.…”
Section: Experimental Settingmentioning
confidence: 99%
“…The electronic pressure-scanning module converts them to high-level electronic signals. This system is a globally proven equipment for wind tunnel experiments in the construction, civil, and aerospace fields [22][23][24][25]. This electronic pressure-scanning module can accurately measure unsteady pressure signals within a small margin of error.…”
Section: Experimental Settingmentioning
confidence: 99%
“…In Table 2, consensus has been achieved on the effects of most of these parameters such as the roof shape, the roof pitch, and the building geometry, while different opinions exist on whether surrounding structures cause enhancement or shielding effects due to the cancellation of various factors. Each of the affecting parameters has been studied including the ratio of building height to mean spacing (e.g., [54]), the interference factor (IF) (e.g., [55]), and the building area density (e.g., [56]). Gavanski et al [52] categorically evaluated such combined actions by comparing measured external pressure coefficient contours from 87 building configurations and concluded that the effect of surrounding structures for design can be neglected.…”
Section: Wind Load Characterizationmentioning
confidence: 99%
“…Liu (2006) considered the ratio of the mean windward area of a building and the mean occupied area as the parameter of building density and performed a wind tunnel test to study the effects of this parameter on the wind pressure coefficients of three zones, namely, corners, eaves, and interior, in the complicated roof of a low-rise building. Pindado et al (2011) analyzed the effect of an upstream building on the suction forces on the flat roof of a low-rise building in the wake. The influence of the distance between both buildings on the wind loads on the downstream building roof was analyzed, including the height of the upstream one and the wind angle of incidence.…”
Section: Wind Tunnel Testmentioning
confidence: 99%